Less Is More? Combined Approaches to Improve Mortality and Morbidity after Aortic Valve Replacement - Elisa Mikus; Mariafrancesca Fiorentino; Diego Sangiorgi; Simone Calvi; Elena Tenti; Andrea Cavallucci; Elena Tremoli; Alberto Tripodi; Maurizio Pin; Carlo Savini (Biomedicines, 2023)
Background: Nowadays, one of the main goals of aortic valve surgery is to reduce the biological impact, mortality, and complications. It is well-known that long operative times in terms of the extracorporeal circulation, but above all, of the aortic cross-clamp time (ACC), represent a risk factor for mortality in patients undergoing cardiac surgery. In order to shorten the aortic cross-clamp time, many technological improvements, such as sutureless prostheses, have been introduced, but their actual effectiveness has not been proven yet. The aim of this study was to assess the 30-day outcomes of patients undergoing aortic valve replacement surgery, focusing on the ACC length. Methods: All 3139 patients undergoing aortic valve replacement between January 2013 and July 2022 at our institution were enrolled. The data were retrospectively collected and the baseline characteristics and intraoperative variables were recorded. In order to adjust the results according to the differences in the baseline characteristics, propensity score matching was performed and four groups of 351 patients were obtained based on the first, second, third, and fourth quartile of the ACC time. Results: The patient population included 132 redo surgeries (9.4%) and 61 cases of active endocarditis (4.3%), with an overall median EuroSCORE II of 1.8 (IQR 1.2–3.1). An increase across the groups was observed in terms of the acute kidney failure (p < 0.001) incidence, the number of blood transfusions (p = 0.022), prolonged hospital stays (p < 0.001), the and respiratory failure (p < 0.001) incidence. A p of < 0.1 was found for the 30-day mortality (p = 0.079). The predictors of an early 30-day mortality were standard full sternotomy (OR 2.48, 95% CI 1.14–5.40, p = 0.022), EuroSCORE II (OR 1.10, 95% CI 1.05–1.16, p < 0.001), and a trend for a longer ACC time (Q4 vs. Q1: OR 2.62, 95% CI 0.89–7.68, p = 0.080). Conclusions: Shortening the operative times resulted in marked improvements of the patients’ outcomes. The combined use of minimally invasive approaches and sutureless aortic valve prostheses allows for a lower 30-day events rate. New technologies should be assessed to obtain the best results with the least risk.